Mosca blanca, Bemisia tabaci / Mosca blanca, ciclo de vida - Hugh A. Smith; Nicole Casuso; Lorena Lopez (EDIS)
Bemisia tabaci, the sweetpotato whitefly, is a serious pest of many horticultural, agronomic and ornamental crops in Florida. This fact sheet aids with identification of the pest.